Regional migration governance in Africa and beyond: a framework of analysis - Eva Dick; Benjamin Schraven (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
In the context of the global refugee crisis, trans-Saharan and trans-Mediterranean (irregular) migration from Africa to Europe has recently received huge public and political attention, particularly within Europe. Calls for reducing and containing irregular migrant flows and addressing the “root causes” of forced migration dominate the European policy discourse. However, migration within the African continent is much more prevalent than migration from Africa to Europe or other parts of the world. About two-thirds of African international migrants are living in another African country. The types of mobility thereby range from seasonal labour migration to forced displacement with varying geographic extensions. Against this background, the African Union has defined norms and strategic guidelines regulating migration and forced displacement and regional organisations such as the Intergovernmental Authority on Development (IGAD) in the Horn of Africa and the Economic Community of West African States (ECOWAS) are involved in migration governance. Regional organisations and migration platforms are gradually becoming acknowledged political players, also reflecting a general trend of regionalisation and pluralisation in international and migration policies. Their actual involvement in global policy processes, such as the currently negotiated Global Compacts for Migration and on Refugees, as well as in EU-Africa migration initiatives remains nonetheless limited. While increasingly recognised, up to present, regional migration regimes outside Europe remain little understood regarding their main drivers, features and impact. The present paper sets the ground for enhancing this understanding by introducing a framework of analysis for regional migration governance. The framework incorporates elements of various approaches to international organisations of which regional organisations (ROs) form a subset. In this context, both institutional characteristics such as organisational identity and history and the interests of (powerful) member states and external actors are considered key explanatory factors for migration-related strategy formulation and implementation. The framework introduced is intended as a general scheme for the analysis of regional migration governance around the globe – not only specifically in Africa. However, in this study, migration governance in the two African sub-regions - Economic Community of West African States (ECOWAS) and the Intergovernmental Authority on Development (IGAD) at the Horn of Africa - is used to illustrate the diversity of historical pathways, migration realities and challenges as well as institutional settings. Whereas the IGAD sub-region is characterised by high levels of forced displacement, the ECOWAS countries have a long tradition of circular and seasonal labour migration, not least mirrored in a relatively established and internally driven migration policy agenda. The paper shows that the framework facilitates a comprehensive understanding of regional migration governance structures and processes. Our hitherto analysis based on the framework indicates that the organisations studied, IGAD and ECOWAS, are well-placed for the management of regional migration. Institutional structures between the two differ, for instance, with regard to levels of legalisation, with ECOWAS disposing of strong formal powers to enforce regional policies and IGAD privileging informal cooperative relationships between member states. Since both regions experience challenges in the implementation of regional norms at national and sub-national levels, (further) financial and technical support in this area is necessary.
Keywords: 330; Regionale + globale + transnationale Governance; Flucht und Migration